MECHANISM OF INJURY IMPACTS CONCUSSION RECOVERY. Issue 7 (30th July 2021) - Caze, Todd J.; Ellis, Christine; Knell, Gregory; ,; Abt, John; Burkhart, Scott
Background: Approximately 2 million children sustain a concussion annually with the majority recovering within 28 days. However, some children take longer to recover suggesting more research is necessary to determine what factors prolonged return to activity/sport. Hypothesis/Purpose: The purpose of this study was to examine the relationship between mechanism of injury (MOI) and protracted recovery (>28 days). It was hypothesized that those who sustained a concussion via head-to-head or head-to-ground were at greater risk of recovery lasting longer than 28 days than other MOIs (head-to-body, head-to-object). Methods: Children aged 8-18 years who sustained a concussion were examined in an acute concussion clinic for diagnosis and treatment of injury. Patients were evaluated within seven days of injury and remained under clinical care until cleared to return to activity/sport. Average days of recovery along with crude hazard ratios were calculated based on MOI. Results: A total of 282 children (age: 13.9±2.2 years) were diagnosed with a concussion. Total recovery was 22.1±11.3 days overall, and by MOI was as follows: head-to-object (n=52, 22.1±12.7 days), head-to-body (n=36, 22.9±11.5 days), head-to-head (n=106, 21.3±10.9 days), head-to-ground (n=79, 22.7±11.0 days). Compared to a head-to-object MOI, the risk (95% CI) of delayed recovery by MOI was as follows: head-to-body (1.75, 0.65-4.70), head-to-head (1.66, 0.72-3.80), head-to-ground (1.70, 0.71-4.06). Conclusion: Contrary to our hypothesis, the head-to-head and head-to-ground MOIs were not associated with a greater risk of a protracted recovery in this sample of adolescents. These preliminary findings suggest that MOI may not be an important clinical indicator when being treated acutely in a specialty concussion clinic. Future research should consider angle and velocity of impact as a factor of recovery.